Strengthening Online Promotions and Improving Service Quality at “Jogja Id Screen Printing” - Leony Permata Setiawati; Audita Nuvriasari (PT FORMOSA CENDEKIA GLOBAL, 2023)
The development of the printing business in the digital era is increasingly rapid along with high consumer demand for using these services. In order for the business to survive in competition, it is necessary to formulate the right marketing strategy. This community service is carried out to improve the performance of the printing business at Sablon Jogja ID through online marketing assistance activities and improving service quality. Activities are carried out using counseling and training methods. Through attractive online promotional activities and satisfactory customer service, companies can build closer relationships with customers, increase customer satisfaction, and ultimately achieve sustainable business growth in this digital era.